IMPROVEMENT OF DIGITAL LITERATION IN ASPECTS OF CREATIVITY THINKING PARTICIPANTS EDUCATION THROUGH PROJECT BASED LEARNING (PBL) IN SOCIAL STUDIES (A Class Action Research Study in SMPN 30 Bandung) - Anggraeni, Resti (International Journal Pedagogy of Social Studies, 2019)
ABSTRACTÂ This study aims to improve 21st century skills in digital literacy on the creativity aspects of students' thinking through project based learning. Creativity in thinking at this time is how to do combinations of various factors in human beings, the environment and the process of technological development that is rapidly changing so that it can produce new works that are useful or have social meaning. The method used is the classroom action research model of Kemmis and Taggart, the study was conducted on students of class VII-D of SMP Negeri 30 Bandung consisting of 32 students. Data collection techniques used are observation, interviews and documentation. The theory used is the theory of skills in processing information from several experts which are then modified by researchers according to the needs of the research. The increase in digital literacy in the aspects of students' creativity in thinking through project based learning in social studies learning, based on indicators of increasing digital literacy that each cycle has increased, from the category of enough with a percentage of 46.6% in the first cycle then in the second cycle increased to 81.6 % in good category and in the third cycle increased to 88%. Based on the presentation above, it can be concluded that there is an increase in digital literacy in the aspects of creativity of students' thinking through project-based learning in social studies learning.Â Keywords: Creativity, digital literacy, project based learning.